Development of a Three-Tier Higher Order Thinking Skills (HOTS) Assessment Instrument on Acid Base Material Assisted by Gimkit - Ananda Emyliah; Jusniar; Ramlawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to describe the development process of a HOTS three-tier assessment instrument on acid-base material assisted by Gimkit and to find out the validity, reliability, and practicality of the HOTS three-tier assessment instrument on acid-base material assisted by Gimkit that was developed. The data source for the validity test came from 2 validators, while the reliability and practicality tests came from 2 subject teachers and 31 11th-grade students of Merdeka 2 at SMA Negeri 1 Campalagian. The reliability and practicality trials were conducted in the even semester of the 2025/2026 academic year. The research method used was a research and development (R&D) with the Plomp model, which includes the preliminary investigation phase through observation and interviews, the design and realization phase covering the design and creation of the HOTS three-tier assessment instrument on acid-base material, and the test, evaluation, and revision phase including validity tests and limited trials to find out reliability and practicality. The developed instruments consist of: (1) instrument grid, (2) HOTS three-tier assessment instrument, (3) answer key, (4) validity sheet, and (5) perception questionnaire. The results show that the HOTS three-tier assessment instrument product is highly valid with an inter-rater reliability value of 1.00, reliable, and very practical. Based on the results, it can be concluded that the instrument can be an important reference for teachers in assessing students’ cognitive aspects and misconceptions.